Basidiocarp structures of Lentinus crinitus: an antimicrobial source against foodborne pathogens and food spoilage microorganisms - Bertéli, Míria B.D. (2022)
Lentinus crinitus basidiocarps are an alternative to antimicrobials, but the stipe (24% basidiocarp) is discarded even with potential antimicrobial activity. This study evaluated the antimicrobial activity of L. crinitus basidiocarp pileus and stipe extracts against foodborne pathogens and food spoilage microorganisms. Basidiocarps of L. crinitus were grown in sugarcane bagasse and rice husks and the pileus and stipe methanolic extract was analyzed by broth microdilution method for antimicrobial activity against eight bacteria and eight fungi. The minimum bactericidal concentration values for pileus and stipe ranged from 0.40 to 0.50 mg mL− 1, for streptomycin from 0.10 to 0.50 mg mL− 1, and for ampicillin from 0.40 to 1.20 mg mL− 1. The minimum fungicidal concentration values for pileus and stipe ranged from 0.06 to 0.60 mg mL− 1, for bifonazole from 0.20 to 0.25 mg mL− 1, and for ketoconazole from 0.30 to 3.50 mg mL− 1. Extracts had bacteriostatic, bactericidal, fungistatic and fungicidal activity against all microorganisms, but with greater efficiency and specificity for some microorganisms. Both pileus and stipe are promising and sustainable alternatives for use in food, agricultural, and pharmaceutical industries.